ANTIPLASMODIAL TRITERPENOIDS ISOLATED FROM CANTHIUM MULTIFLORUM - Traoré, M.; Ziegler, H. L.; Olsen, C. E.; Millogo, H.; Ouédraogo, J. B.; Guissou, I. P.; Nacoulma, O. G.; Guiguemdé, T. R.; Christensen, S. B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In Burkina Faso, roots of Canthium multiflorum (Thonn.) Hiern (Rubiaceae) are used for the treatment of malaria and hypertension [1]. This investigation was initiated because of the absence of published phytochemical reports on this species and the possibility of the presence of antiplasmodial compounds. A bioactivity guided fractionation of roots of Canthium multiflorum led to the isolation of the 2 new ursenoic acid derivatives, 19α-hydroxy-3-oxo-ursa-1,12-dien-28-oic acid 1 and 3-oxo-15α,19α-dihydroxyursa-1,12-dien-28-oic acid 2 which were tested for antiplasmodial effect and for inducing change of the shape of membranes of erythrocytes. Assay for antiplasmodial activity was performed using chloroquine-sensitive Plasmodium falciparum strain 3D7 [2]. Chloroquine was used as a positive control. Investigation of membrane shape effects of pentacyclic triterpenes was performed according to a previous described method (Ziegler et al., 2002) [3]. The structure of the two new compounds was elucidated using MS and NMR spectroscopy. The HR-ESI-MS gave a m/z 467.3161, calcd. for C30H43O4 (M-H)- 467.3167 for 1 and m/z = 507.3089 [M+ Na]+ (calcd. for C30H44NaO5 :507.3081) for compound 2. Application of the modified octant rule and comparison of the recorded CD spectrum with those of related pentacyclic triterpenoids with a 1-en-3-one system in the A-ring confirmed the absolute configuration of the two compounds. A moderate antiplasmodial activity (IC50=26 μg/ml) was observed which was not related to the deformation of the shape of erythrocyte membranes. References: 1. Nacoulma, O.G. (1996). Plantes médicinales et pratiques médicinales traditionnelles au Burkina Faso: Cas du plateau central. Faculté des Sciences et Techniques, Université de Ouagadougou. 2. Ziegler, H.L., Staerk, D., Christensen, J. et al. (2002b). Antimicrobial Agents and Chemotherapy, 46, 1441–1446. 3. Ziegler, H.L., Jensen, T.H., Christensen, J., Staerk, D. et al. (2002a). Planta Medica, 68, 547–549. Acknowledgments: This work was supported by Danida. We thank Dorte Brix for technical support.